2022
DOI: 10.1002/ange.202114167
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Receptor Mobility in Multivalent Binding on Lipid Membranes

Abstract: Numerous key biological processes rely on the concept of multivalency, where ligands achieve stable binding only upon engaging multiple receptors. These processes, like viral entry or immune synapse formation, occur on the diffusive cellular membrane. One crucial, yet underexplored aspect of multivalent binding is the mobility of coupled receptors. Here, we discuss the consequences of mobility in multivalent processes from four perspectives: (I) The facilitation of receptor recruitment by the multivalent ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…When studying systems with fewer receptors their mobility could start to play a role in selectivity as polymers recruit nearby receptors. Previous studies have shown that receptor mobility can enhance ( α ) selectivity and shift the selectivity maximum to a lower number of receptors. , In the cases where receptors are in fixed positions, large inhomogeneities in those positions could also affect results, with recent work showing that uniformity in the receptor distribution can enhance selectivity. , …”
Section: Resultsmentioning
confidence: 99%
“…When studying systems with fewer receptors their mobility could start to play a role in selectivity as polymers recruit nearby receptors. Previous studies have shown that receptor mobility can enhance ( α ) selectivity and shift the selectivity maximum to a lower number of receptors. , In the cases where receptors are in fixed positions, large inhomogeneities in those positions could also affect results, with recent work showing that uniformity in the receptor distribution can enhance selectivity. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, biosystems functioning on transistors have the potential to simulate their operation in living organisms. It has been revealed that the mutivalent binding at biointerfaces is the prevalent mode in wide-ranging biological processes, enabling strong and highly selective interactions. , In particular, envelope protein is the main ligand at the biointerface of a biosystem responsible for the interaction with their specific receptors to establish biological processes. , Thus, constructing a multivalent interface between the envelope protein and transistor is highly demanded to build intelligent bioelectronic systems.…”
mentioning
confidence: 99%